MiR-548c-3p through suppressing Tyms and Abcg2 increases the sensitivity of colorectal cancer cells to 5-fluorouracil - Elham Khalili; Ali Afgar; Azam Rajabpour; Seyed Hamid Aghaee-Bakhtiari; Khadijeh Jamialahmadi; Ladan Teimoori-Toolabi (Heliyon, 2023)
Background: Colorectal cancer, is one of most prevalent the cancer in the world. 5-Fluorouracil is a standard chemotherapeutic drug while the acquisition of resistance to 5-Fluorouracil is one of the problems during treatment. In this study, we aimed to find the miRNAs that modulate the expression of Tyms and Abcg2 as resistance-inducing genes in the resistant cell lines to 5-Fluorouracil. Methods: 5-Fluorouracil-resistant HCT116 and SW480 cell lines were generated by consecutive treatment of cells with 5-Fluorouracil. This resistance induction was validated by MTT assays. The expression of the Tyms and Abcg2 gene and miR-548c-3p were studied by quantitative real-time PCR in the cell lines. Results: We hypothesized that miR-548c-3p is targeting Tyms and Abcg2 simultaneously. Increased expression Tyms gene in the two most resistant cell lines derived from HCT116 and all resistant cell lines derived from SW480 except one were seen. Increased expression of Abcg2 was observed in the most resistant HCT116-derived cell line and all resistant cell lines, derived from SW480. In all resistant cell lines, the expression of miR-548c-3p was decreased. Conclusion: It can be concluded downregulation of miR548c-3p is in line with Tyms and Abcg2 overexpression in resistant cell lines to 5-Fluorouracil.